The Role of Local Wisdom Based School Culture in Enhancing Students’ Discipline and Learning Motivation - Burhan Burhan; Herwandi Sape; Risqah A Kasman; Murniaty Murniaty (ITEKES Permata Ilmu Maros, 2025)
This study investigated the role of local wisdom–based school culture in improving students’ discipline and learning motivation. The research aimed to identify the forms of local cultural values implemented in the school, examine strategies used in applying those values, and analyze their impact on students’ academic behavior. The study employed a descriptive qualitative approach to explore the phenomenon naturally and understand the meaning behind the actions and experiences of the participants. Data were collected through observations of school cultural activities, in-depth interviews with the principal, five teachers, and ten students, and documentation of school records and relevant programs. The findings revealed that the school implemented several forms of Bugis local wisdom, including the values of siri’ na pacce, mutual cooperation (massiddeng), politeness through greeting habits, religious routines, and the use of local language as a cultural preservation approach. These values were integrated through exemplary leadership, structured habituation, curriculum and extracurricular programs, and collaboration with parents and the community. The results indicated a significant improvement in student discipline, demonstrated by a decrease in rule violations and an increase in responsibility and punctuality. Additionally, students’ learning motivation increased due to a positive school climate, emotional bonding with the school, and cultural identity pride. The study concluded that school culture based on local wisdom served as an effective strategy for character building and enhancing academic motivation, and it is recommended to be implemented sustainably in schools.